Resident evil : the final chapter [videorecording (Blu-Ray)] - Anderson, Paul, 1965-; Anderson, Paul, 1965-; Anderson, Paul, 1965-; Jovovich, Milla; Glen, Iain, 1961-; Larter, Ali, 1976- (Sony Pictures Home Entertainment, 2017)
Alice discovers that she must return to Raccoon City to fight against the Umbrella Corporation and their final attack against the survivors of the zombie virus.